Maternal Factors Influencing Infant Oral Health Knowledge and Beliefs among Pregnant Women in Saudi Arabia: A Cross-Sectional Study - Shekhar, Madiraju Guna; Alhowail, Abdulhakim Essa; Almugla, Yousef Majed; Abraham, Sajith (European Journal of General Dentistry, 2025)
This study aimed to assess the knowledge and beliefs regarding infant oral health care among Saudi pregnant women and identify influencing factors.A cross-sectional study was conducted on 235 pregnant Saudi women attending prenatal clinics in AlAhsa, Eastern region of Saudi Arabia from November 2023 to March 2024. Data were collected using a validated, self-administered questionnaire assessing demographic information, infant oral health knowledge (IOK), and infant oral health beliefs (IOB). Data were analyzed using chi-squared tests and multiple linear regression.The mean age of participants was 29.27 ± 3.45 years, with 56.5% being multiparous. Most respondents (64.1%) had completed college or university education. Only 36.3% reported regular dental visits during pregnancy. Multiparous women demonstrated significantly higher IOK scores compared with primiparous women (p = 0.013), while IOB scores were comparable (p = 0.087). Regression analysis revealed that birth history and education significantly predicted IOK scores (R2 = 0.561; p < 0.001), while education, maternal age, and dental visits during pregnancy significantly predicted IOB scores (R2 = 0.266; p < 0.001).This study highlights the significant influence of birth history, education, maternal age, and dental visits during pregnancy on maternal knowledge and beliefs regarding infant oral health. These findings underscore the need for targeted, culturally sensitive educational interventions and increased health care provider engagement to promote oral health awareness and behaviors among pregnant women in Saudi Arabia.
Keywords: infant oral health; pregnant women; knowledge; beliefs; birth history; parity